일제 강점기 익산 지역의 교육 인프라와 사학(私學)운동 - 김귀성(Kim, Gui-Sung) (열린정신 인문학 연구, 20(3), 2019)
이 논문은 일제 강점기 익산 지역의 교육 인프라와 사학운동을 밝혀보는데 그 목적을 두고 있다 일제 강점기 익산 지역은 유구한 역사와 다종교문화의 고장 천혜의 광활한 농업기반 도시와 인구의 증점 지역 ,사통팔달 교통의 요충지로써 당시 교육에 직 간접적인 영향을 미친 것 · 으로 이해된다 한편 일제강점기 교육을 지배해온 것은 일제가 공포한 각종 교육 관련 법규들이었다 이런 상황 속에서도 일제에 의한 관 공립학교의 설립 및 운영과 대조적으로 각종 사립학교 서당 사설강습회 및 야학 유치원 등의 설립과 운영은 이 지역 사학교육 운동을 주도했다. 그렇지만 제반 여건에서 전자에 비해 열약한데다 오늘의 교육과는 단절된 역사를 안고 있다 이런 한계 속에서도 공립학교를 비롯하여 고등교육을 청원하는 노력까지 기울인 점은 이루지 못한 꿈으로 남아 있다. 특히 사학운동과 관련하여 주목할 만한 것은 익산 지역에 많은 각종 사립학교들이 종교단체 지역 유지 단체에 의해 설립 운영되었다는 점 , 교육의 소외지대에 서당을 설립하여 운영한 점 각종 강습회 및 야학을 운영한 점 등은 시사하는 바가 크다 이제 일제 강점기 익산 지역의 교육 인프라와 사학운동을 정리하면서 몇 가지 과제와 시사점을 제시하면첫째 익산 지역의 교육 인프라를 최대한 계승 발전시키는 노력이 요구된다. 둘째 익산 지역의 사학운동의 저변에 스며있는 교육 혼을 계승, 발전시키는 일이다 끝으로 익산 지역의 교육발전을 위한 교육 공공성의 공유지대를 보다 확고히 하는 점이다. The purpose of this paper examine the educational infra-structure and private education movement of IkSan District under the Japanese Colonial periods. As we know, IkSan District in the Japanese Colonial periods had a history from time immemorial and multi-religious culture, a vast plain agricultural city, traffic city to be accessible from all directions. Those education infra-structure effected upon education at that time. However it dosn't limited only to IkSan district, most of all occupied education under the Japanese Colonial periods were various laws and regulations proclaimed by Japanese Imperialism : Act of private schools, from the first Act of ChoSun Education to the fourth Act of ChoSun Education, village schools, local schools annexed to the Confucian shrine, regulations on private short term courses. Among those situations, contrast with government and public schools run by Japanese imperialism, those education movement run by non-government support, poor than former in each environment compared with former schools. But under the those situations, even not accomplished the aims, taken an remarkable things were the petition presented by private education institutes about the establishing public schools and private higher education. Especially, private education movement give us implications so much: a lots of private schools established and run by religious groups, some private schools established by influential person and groups in IkSan districts, on the other hand the village schools established at the rural area, various private short term courses and night schools also established. However remained tasks will be studied at near future are as following: How such persons related with private education movement, curriculum management, evaluation at that times, resistence movement against Japanes imperialism. Now I'd like to present the some implication for Development of Education in IkSan districts as follows. First, let's take over the such an education infrastructure in Japanese Colonial periods and take an effort to development of education in Iksan district. Second, let's think about how to succeed and develope the spirit of education in Iksan district impressed in mind. Finally, for that, community members should be firmed and hold in public interest in common, overcome the regional bound, private education movement in Japanese imperialism were not pursuit for the personal development or interest, but only for development of community. It already have stopped the colonialism in political sense, but in cultural and economic sense, such colonialism not yet recovered. For those, much more important thing is to be an extension of public mind for the regional and community. KCI Citation Count: 0